Komunikowanie dobra w świetle podmiotowości kompetencji komunikacyjnych - inspiracje personalistyczne = Communication of the good in the light of subjectivity of communication competencies - personalistic inspirations - Drąg, Katarzyna; Drożdż, Michał (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The space of media and social communication, as the basic space of human life in the information civilization, is also a space of values. The aim of the article is to show good as the Basic ethical value present in the space of social communication from the perspective of the subjectivity of the human person.
Keywords: prawda; dobro; piękno; wartość; media; komunikacja społeczna; kompetencje komunikacyjne; osoba; komunikowanie interpersonalne; truth; good; beauty; values; social communication; communication skills; person; interpersonal communication